Improving the Performance of the European Social Model - The Welfare State over the Life Cycle - Assar Lindbeck (The Research Institute of Industrial Economics (IUI), 2003)
The achievements of social-welfare arrangements in Western Europe are well known: considerable income security, relatively little poverty and, in some countries, ample supply of social services. But there are also well-known weaknesses and hence considerable scope for improvement. Three types of weaknesses are considered in this paper: social-welfare arrangements are often not financially robust to shocks; individuals make undesirable behavioural adjustments in response to welfare-state arrangements and their financing; and social-welfare arrangements are often poorly adapted to recent changes in socio-economic conditions and preferences of individuals. I discuss these weaknesses, and alternative methods to mitigate them, in the context of various types of welfare-state arrangements that the individual may encounter over the life cycle.
Keywords: H00; H40; H50; 330; Social Policies; Welfare State; Labour Market; Family Structure; Preferences; Sozialpolitik; Sozialstaat; Arbeitsmarkt; Familiensoziologie; Europa